Beliefs About Emotion Are Tied to Beliefs About Gender: The Case of Men’s Crying in Competitive Sports - MacArthur, Heather J. (Frontiers in Psychology, 2019)
Gender and emotion stereotypes suggest that men do not and should not cry, yet men’s crying seems to be particularly prominent in contexts such as competitive sports. In two studies, I investigated the possibility that men’s crying is more frequent and seen as more acceptable in these settings because such contexts are perceived to be highly masculine, and can buffer men from the negative consequences associated with violating gender stereotypes. Specifically, I tested the hypotheses that (a) observers would perceive men’s crying more positively in a masculine-stereotyped than a feminine-stereotyped setting, and following from this, (b) men would report being more likely to shed tears in a stereotypically masculine than a stereotypically feminine setting. To test these predictions, I conducted two between-subjects experiments in which participants (N = 250; N = 192), read a vignette about a man or a woman crying in either a stereotypically masculine (firefighting, weightlifting) or stereotypically feminine (nursing, figure skating) setting, and then rated the target on several emotion-related dependent variables. In line with predictions, results of Study 1 indicated that participants rated crying male firefighters as more emotionally appropriate, emotionally strong, and as higher in workplace status than crying male nurses, and that these effects were mediated by perceptions of the target’s masculinity and femininity. Study 2 replicated these effects using sports-related vignettes, and showed that male participants reported being more likely to shed tears after losing a competition in weightlifting than in figure-skating. Taken together, these findings suggest that men who are perceived to embody cultural ideals of masculinity may be given more room to cry than those who are perceived as less stereotypically masculine.